Diversity and Host Ranges of Whiteflies in Mekarsari Fruit Park, Bogor: a Comprehensive Study of 20 Whitefly Species Across 56 Fruit Plant Species - Purnama Hidayat; Nurjanah; Revhida Puspa Anisa (Andalasian International Journal of Entomology, 2024)
Mekarsari Fruit Park, situated in Bogor, boasts an extensive collection of 226 fruit species. Apart from vegetables and ornamentals, fruit plants play a significant role as hosts for whiteflies. Whitefly infestations can disrupt photosynthesis and respiration, affect the aesthetics of ornamental plants, and transmit plant diseases caused by viruses. The primary objective of this study was to assess the species diversity of whiteflies and their host ranges within Mekarsari Fruit Park. Purposive sampling was employed, followed by preparing collected samples for microscope slides and identification. A total of 20 whitefly species were collected from 56 fruit plant species spanning 20 different families. Of the 20 collected species, 16 were successfully identified, while four remained morphospecies. These whiteflies were categorized into two subfamilies: 17 species belonging to the Aleyrodinae subfamily and three species belonging to the Aleurodicinae subfamily. Paraleyrodes minei emerged as the most prevalent whitefly species, infesting 14 host plants across 11 families. Furthermore, the study revealed that 14 whitefly species were found exclusively on one fruit plant species, one whitefly species on two fruit plant species within the same family, and seven whitefly species on multiple fruit plant families. The Euphorbiaceae and Rubiaceae families were the most susceptible to whitefly infestation among the fruit plants.